(A)historične perspektive afriško ameriške književnosti - Kočan, Kristina (Primerjalna književnost, 2015)
The cultural valorization of African American literature has always been problematic because of the political and sociocultural circumstances. This article addresses the issue of African American literature as a historical phenomenon and opposes Kenneth W. Warren's bold claim that African American literature came to an end with desegregation.
Keywords: Warren, Kenneth W.; književnost in družba; afroameriška književnost; afroameriška poezija; kulturno vrednotenje; literarni kanon; historičnost; ahistoričnost